PEMBUATAN PETA SITUASI SKALA 1:500 DUSUN PURWOSASONO DESA BELUK KECAMATAN BAYAT KABUPATEN KLATEN PROVINSI JAWA TENGAH - , M.ATHA RABBITA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This final task describes the work practices of the field work that have been implemented include the measurement and mapping the situation on one area measuring approximately 1 hectare, and to obtain information on the location of the spatial data by performing a measurement framework that includes control map, high points and details of planimetris is obtained from the measurement of the Earth's surface that has been presented in the form of a map. The method used is the making of the control framework map in the form of a horizontal control framework, measurement framework the control vertically, and detailed measurements of the planimetris, as well as the depiction of a digital situation map. The results already obtained is a map of the situation which presents a spatial surface of the Earth at the hamlet of purwosasono, the village of outs, sub bayat, klaten Regency, Central Java province by using digital situation map making in large scale 1: 500, using a UTM projection system (Universal Transverse Mercator) zone 49S and datum WGS ' 84 (World Geodetic System).